EVALUASI PENGANGGARAN DAN PELAKSANAAN ANGGARAN ORGANISASI SEKTOR PUBLIK (STUDI PADA LEMBAGA ILMU PENGETAHUAN INDONESIA) - Ika Aristiowati (Master in Accounting Program, 2014)
This study aims to get in-depth understanding on budgeting and budget execution carried out by Working Unit (Satker) of Social Sciences and Humanities (IPSK) of LIPI for 2014 period, which including processes, problems, and the efforts taken. The other aim is to obtain evidence regarding the existence of isomorphism and identify the dominant isomorphism pressure found in the practice of budgeting and budget execution in IPSK working unit of LIPI. The theory development and interpretation of this study are based on the theories of public sector budget, accounting behaviour, and institutional isomorphismThe sample used in this study consisted of researchers and financial managers who understand and directly involved in the processes of budgeting, budget execution and becomes parties who often have different perceptions in terms of budget on IPSK working unit of LIPI. This study uses qualitative method with case study approach. Analysis of qualitative data towards the interview results is conducted with thematic analysis, while the concept of Logic Model and Program Logic Model were used to analyze the practice of budgeting.The study results showed that IPSK working unit of LIPI for 2014 period has met the requirements on budgeting and budget execution according to the prevailed regulations. In addition, there are still many problems in budgeting and budget execution within IPSK working unit of LIPI, especially in its relation to human behaviour. Concepts of Logic Model and Program Logic Model were proved to be relevant to mediate differences in perceptions that arise between researchers and financial managers in the process of budgeting and budget execution. The analysis also shows that there is isomorphism existed in budgeting and budget execution conducted by IPSK working unit of LIPI, which is more dominant than coercive, mimetic, and normative pressures.